Recreational drug use among individuals living with HIV in Europe: review of the prevalence, comparison with the general population and HIV guidelines recommendations - Garin, Noe; Velasco, Cesar; De Pourcq, Jan T.; Lopez, Belen; Gutierrez, Maria del Mar; Haro, Josep M.; Feliu, Anna; Mangues, Maria A.; Trilla, Antoni (Frontiers in Microbiology, 2015)
BACKGROUND Adherence problems, interactions and higher rate of risk activities have been observed in HIV individuals using recreational drugs. Our aim was to describe recreational drug use in both HIV individuals and general population in Europe, and to assess at what extent HIV guidelines address this issue. METHODS Data on recreational drug use across Europe were obtained from the European Monitoring Centre for Drugs and Drug Addiction for the general population, and through Pubmed search. for HIV patients. We assessed the incorporation of recreational drug issues in HIV treatment guidelines for the following topics: a) recreational drugs; b) adherence to antiretrovirals; c) interactions; d) transmission risk. Guidelines included: World Health Organization; European Aids Clinical Society; U.S. Department of Health and Human Services; International Antiviral Society-USA; and seven European national guidelines. RESULTS 29 countries reported recreational drug use in general population. The highest prevalences were observed for Cannabis (i.e. 8-10% in Spain, France and Czech Republic) followed by cocaine, amphetamines and ecstasy. The 13 studies selected in the systematic review showed a great variability in recreational drug use on the HIV population. Apart from classical recreational drugs, we found a relevant use of new drugs including sexual experience enhancers. Polydrug consumption was about 50% in some studies. Most guidelines included general information about recreational drugs, showing great variability on the inclusion of the evaluated topics. We found more specific, evidence-based recommendations on interactions, followed by medication adherence and transmission risk. CONCLUSIONS Available data on the people living with HIV suggest a higher use of recreational drugs than in the general population, which is already relevant. However, recreational drug issues should be included or addressed more thoroughly in most guidelines.